The production and pricing strategy of the two-echelon remanufacturing supply chain with~government subsidy under~patent protection - Xiaogang Cao; Hui Wen; Bowei Cao (Modern Supply Chain Research and Applications, 2023)
Purpose - In this paper, the authors study the production and pricing decisions of a remanufacturing supply chain composed of a supplier, an assembler and a remanufacturer, in which the remanufacturing of components requires patent licensing from the supplier. Design/methodology/approach - The authors consider three different models with government subsidy for remanufacturing: (1) no government subsidies; (2) the government subsidizes the remanufacturing behavior of the supplier and (3) the government subsidizes the remanufacturing behavior of the remanufacturer and use the Stackelberg game model to solve and analyze the equilibrium wholesale prices of components and the equilibrium outputs of new and remanufactured products under three subsidy modes. Findings - The results show that the equilibrium wholesale prices of two kinds of components decrease with the unit patent licensing fee and the unit government subsidy, and the equilibrium quantity of the remanufactured products under the three modes is obviously higher than that of the new products. Originality/value - Finally through numerical simulation, it is found that the equilibrium profits of the supplier, the manufacturer and the supply chain increase monotonously in relation to the unit government subsidy, while the optimal profit of the assembler in relation to the unit government subsidy tends to decrease first and then increase.
Keywords: 650; Cournot competition; Government subsidy; Patent licensing; Stackelberg game; Two-echelon remanufacturing